PENGARUH PEMBERIAN REWARD, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi pada PT. Kereta Api Indonesia di Surakarta cabang Purwosari) - EviTriana Mayang Sari; Kusdiyanto Kusdiyanto (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
This study aims to determine the effect of reward, work motivation, and leadership style on employee performance of PT Kereta Api Indonesia in Surakarta Purwosari Branch. This research uses quantitative research methods. Researchers collect questionnaire data directly to respondents, namely by distributing the questionnaire to employees. In this study, the population is all employees of PT Kereta Api Indonesia Purwosari branch in Surakarta, totalling 37 employees. The sample in this study were all employees of PT. Kereta Api Indonesia Purwosari branch in Surakarta, totalling 37 employees. This research data analysis uses the SmartPLS 3.0 software application. The results of this study Rewarding has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on employee performance. In conclusion, there is an influence of reward giving, work motivation and leadership style on employee performance